The Role of E-Services, Quality System and Perceived Value on Customer Satisfaction: An Empirical Study on Indonesian SMEs - Aditi, Bunga; Hafizah, Hafizah; Hermansyur, Hermansyur (AGUSPATI Research Institute, 2021)
The purpose of this study is to analyze e-service, system quality, perceived value and satisfaction for customer of Indonesian SMEs. This research was conducted by distributing 140 online questionnaires to customer of Indonesian SMEs and there were 124 questionnaires that were reversed and processed. Sampling method with snowball sampling. The test was carried out with the help of a statistical tool in the form of Structural Equation Modeling (SEM) based on Partial Least Square version 3. The results showed that Based on the results of the hypothesis testing, there was a positive and significant relationship between E-Service and Perceived Value. there was a positive and not significant relationship between System Quality and Perceived Value. that there was a positive and significant relationship between perceived value and e-satisfaction. there was a positive and significant relationship between E-Service and e-satisfaction through perceived value. This study found that e-service has a positive and significant impact on e-satisfaction through perceived value. There are a positive and not significant relationship between system quality and e-satisfaction through perceived value. The novelty of this research is the correlation model of effect of e-service, system quality and perceived value on e-satisfaction of SMEs.